Distance education students’ structured query language achievements and attitudes toward web‐based instruction: Second Life versus the Enocta learning management system/adobe connect - Ozonur, Mesut; Sancar‐Tokmak, Hatice; Yanpar‐Yelken, Tugba (Computer applications in engineering education, 2022)
This study aimed to investigate the effects of instruction offered via different learning environments Second Life (SL) as a 3D world versus Enocta learning management system (LMS)/Adobe Connect Pro as a web‐based environment on distance education students’ academic achievement related to structured query language (SQL) and attitudes toward web‐based instruction. The study used the embedded experimental model. A total of 60 distance education students participated in the study. Based on their pretest academic achievement scores, 30 students were assigned to the experimental group who took the SL class while 30 were assigned to the control group who took the Enocta LMS/Adobe Connect Pro class. The same instructor taught the same course, Database 211, using the same instructional methods and materials but different learning environments (SL for the experimental group and Enocta LMS/Adobe Connect Pro for the control group). The data were collected using the web‐based instruction attitude scale, an academic achievement test on database and SQL, in addition to an open‐ended questionnaire. The results showed that there was no statistically significant difference between the experimental and control groups in terms of academic achievement. However, in terms of attitudes toward web‐based instruction, a statistically significant difference was found between the experimental and control groups in favor of the experimental group.